Long-term tracing of Rhizophagus irregularis isolate BEG140 inoculated on Phalaris arundinacea in a coal mine spoil bank, using mitochondrial large subunit rDNA markers - Sýkorová, Zuzana; Börstler, Boris; Zvolenská, Soňa; Fehrer, Judith; Gryndler, Milan; Vosátka, Miroslav; Redecker, Dirk (Mycorrhiza, 2012)
During the last decade, the application of arbuscular mycorrhizal fungi (AMF) as bioenhancers has increased significantly. However, until now, it has been difficult to verify the inoculation success in terms of fungal symbiont establishment in roots of inoculated plants because specific fungal strains could not be detected within colonized roots. Using mitochondrial large subunit ribosomal DNA, we show that Rhizophagus irregularis (formerly known as Glomus intraradices) isolate BEG140 consists of two different haplotypes. We developed nested PCR assays to specifically trace each of the two haplotypes in the roots of Phalaris arundinacea from a field experiment in a spoil bank of a former coal mine, where BEG140 was used as inoculant. We revealed that despite the relatively high diversity of native R. irregularis strains, R. irregularis BEG140 survived and proliferated successfully in the field experiment and was found significantly more often in the inoculated than control plots. This work is the first one to show tracing of an inoculated AMF isolate in the roots of target plants and to verify its survival and propagation in the field. These results will have implications for basic research on the ecology of AMF at the intraspecific level as well as for commercial users of mycorrhizal inoculation.
Keywords: Phalaris; Base Sequence; ribozomální DNA; DNA, Ribosomal; polymerázová řetězová reakce; Mitochondria; DNA, Mitochondrial; Polymerase Chain Reaction; Glomeromycota; těžba uhlí; Molecular Sequence Data; DNA, Fungal; Symbiosis; půdní mikrobiologie; mykorhiza; mitochondrie; Phylogeny; Mycorrhizae; molekulární sekvence - údaje; Plant Roots; Haplotypes; Czech Republic; Coal Mining; Sequence Alignment; mitochondriální DNA; sekvence nukleotidů; Soil Microbiology; Sequence Analysis, DNA; Česká republika; DNA fungální; symbióza; genetické markery; haplotypy; sekvenční analýza DNA; fylogeneze; kořeny rostlin; sekvenční seřazení; Genetic Markers